Masked CKD in hyperthyroidism and reversible CKD status in hypothyroidism - Uchiyama-Matsuoka, Natsumi; Tsuji, Kenji; Uchida, Haruhito A.; Kitamura, Shinji; Itoh, Yoshihiko; Nishiyama, Yuki; Morimoto, Eisaku; Fujisawa, Satoshi; Terasaka, Tomohiro; Hara, Takayuki; Ogura-Ochi, Kanako; Inagaki, Kenichi; et al. (Frontiers in Endocrinology, 2022)
Introduction: While it is well known that thyroid function may affect kidney function, the transition of the chronic kidney disease (CKD) status before and after treatment for thyroid disorders, as well as the factors affecting this change, remains to be explored. In the present study, we focused on the change in kidney function and their affecting factors during the treatment for both hyperthyroidism and hypothyroidism. Methods: Eighty-eight patients with hyperthyroidism and fifty-two patients with hypothyroidism were enrolled in a retrospective and longitudinal case series to analyze the changes in kidney function and their affecting factors after treatment for thyroid disorders. Results: Along with the improvement of thyroid function after treatment, there was a significant decrease in estimated glomerular filtration rate (eGFR) in hyperthyroidism (an average ΔeGFR of -41.1 mL/min/1.73 m2) and an increase in eGFR in hypothyroidism (an average ΔeGFR of 7.1 mL/min/1.73 m2). The multiple linear regression analysis revealed that sex, eGFR, free thyroxine (FT4) and free triiodothyronine (FT3) could be considered independent explanatory variables for ΔeGFR in hyperthyroidism, while age, eGFR, and FT3 were detected as independent explanatory variables in hypothyroidism. In addition, the stratification by kidney function at two points, pre- and post-treatment for thyroid disorders, revealed that 4.5% of the participants with hyperthyroidism were pre-defined as non-CKD and post-defined as CKD, indicating the presence of “masked” CKD in hyperthyroidism. On the other hand, 13.5% of the participants with hypothyroidism presented pre-defined CKD and post-defined non-CKD, indicating the presence of “reversible” CKD status in hypothyroidism. Conclusions: We uncovered the population of masked CKD in hyperthyroidism and reversible CKD status in hypothyroidism, thereby re-emphasizing the importance of a follow-up to examine kidney function after treatment for hyperthyroidism and the routine evaluation of thyroid function in CKD patients as well as the appropriate hormone therapy if the patient has hypothyroidism.